Numerical investigation on the combustion and emission characteristics of ammonia in a low-speed two-stroke marine engine - Liu, Long; Wu, Yue; Wang, Yang (Fuel (Guildford), 2022)
•A skeleton mechanism of ammonia-diesel was innovatively developed.•Ammonia can be applied on Marine engines by using premixed dual-fuel mode.•Combustion and emissions performance are better in liquid ammonia supply.•The NOx emissions level with SCR after- treatment can meet Tier III limits. Aiming to investigate the application feasibility of ammonia in the low-speed two-stroke marine engine theoretically, an ammonia engine model was constructed to evaluate the performance and emissions characteristics of ammonia engine. The model is based on a premixed dual-fuel engine ignited by the pilot fuel (diesel) injected into the prechamber. A skeletal mechanism with reasonable accuracy containing 104 species and 573 reactions was innovatively developed to simulate the combustion process. Meanwhile, the viability and comparison of various ammonia supply methods including liquid and gaseous forms were explored in terms of engine power, escaped and unburned ammonia, NOx and carbon emissions. The result revealed that the ammonia engine, whether supplied in liquid or gaseous form, can achieve typical ship engine load range and thermal efficiency. Whereas, the supply method of liquid ammonia is superior to gaseous ammonia in terms of power, unburned and escaped ammonia, and thermal efficiency.Furthermore, the NOx and CO2 emissions level of ammonia engine was assessed. The NOx emissions of this operation mode can fulfill the Tier Ⅱ emission limit.